2021
DOI: 10.1016/j.learninstruc.2020.101396
|View full text |Cite
|
Sign up to set email alerts
|

The inattentive on-screen reading: Reading medium affects attention and reading comprehension under time pressure

Abstract: This study explored the influence of reading media and reading time-frame on readers' on-task attention, metacognitive calibration, and reading comprehension. One hundred and forty undergraduates were allocated to one of four experimental conditions varying on the reading medium (in print vs. on screen) and on the reading time-frame (free vs. pressured time). Readers' mindwandering while reading, prediction of performance on a comprehension test, and their text comprehension were measured. In-print readers, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 58 publications
1
52
2
2
Order By: Relevance
“…In addition, we expected that among the participants who were asked to think aloud, participants reading in print would differ from those reading digitally with respect to strategic text processing, particularly with respect to deeper level strategies as revealed by inferences assumed to support mental model construction (e.g., backward, forward, and elaborative inferences; van den Broek, Fletcher, & Risden, 1993). We also grounded this hypothesis in the shallowing hypothesis (Annisette & Lafreniere, 2017) and prior empirical work consistent with this hypothesis (e.g., Ackerman & Goldsmith, 2011;Dahan Golan et al, 2018;Delgado & Salmerón, 2021;Halamish & Elbaz, 2020;Latini et al, 2020), which suggested that a lack of deep reading and, hence, more reliance on superficial text processing when reading on-screen is responsible for observed reading medium differences in comprehension performance. How ever, this is the first study to directly test the shallowing hypothesis by examining qualitatively different forms of text processing across the two reading mediums.…”
Section: The Present Studymentioning
confidence: 71%
See 1 more Smart Citation
“…In addition, we expected that among the participants who were asked to think aloud, participants reading in print would differ from those reading digitally with respect to strategic text processing, particularly with respect to deeper level strategies as revealed by inferences assumed to support mental model construction (e.g., backward, forward, and elaborative inferences; van den Broek, Fletcher, & Risden, 1993). We also grounded this hypothesis in the shallowing hypothesis (Annisette & Lafreniere, 2017) and prior empirical work consistent with this hypothesis (e.g., Ackerman & Goldsmith, 2011;Dahan Golan et al, 2018;Delgado & Salmerón, 2021;Halamish & Elbaz, 2020;Latini et al, 2020), which suggested that a lack of deep reading and, hence, more reliance on superficial text processing when reading on-screen is responsible for observed reading medium differences in comprehension performance. How ever, this is the first study to directly test the shallowing hypothesis by examining qualitatively different forms of text processing across the two reading mediums.…”
Section: The Present Studymentioning
confidence: 71%
“…This difference was based on piloting of the materials, which indicated that a time limit of eight minutes would allow all students to read the entire text and that the average additional time used to think aloud was approximately seven minutes. These time limits were intended to make participants in all conditions experience a certain time pressure because reading medium effects have been found to be more pronounced when reading times are restricted (Delgado et al, 2018; see also Delgado & Salmerón, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…As suggested by the shallowing hypothesis, a frequent use of digital media fosters shallow thought and decreases people's tendency to use reflective thought (Annisette and Lafreniere, 2017 ). This way of thinking is often induced by time constraints as studies have shown lower reading comprehension and less successful problem solving on screen when participants faced time pressure (e.g., Sidi et al, 2017 ; Delgado and Salmerón, 2021 ). In addition, people who often use social media tend to prefer morally shallow life goals such as hedonism and image over goals related to morality and aesthetics.…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…The massive information flow, being the result of digitalization, has been instigating fragmentary understanding of written language and poor consolidation of the received information (cf. Delgado, Salmerón, 2021;Kekeeva, Darzhinova, Abdiraimova, 2020).…”
Section: Introductionmentioning
confidence: 99%